2001
DOI: 10.1038/sj.onc.1204834
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Jak2 tyrosine phosphorylation in Bcr–Abl transformation

Abstract: We have previously reported that the Jak2 tyrosine kinase but not Jak1 is tyrosine phosphorylated in the absence of IL-3 in Bcr ± Abl positive M3.16 cells, which are rendered IL-3 independent by BCR ± ABL gene expression. We have explored the involvement of Jak2 tyrosine phosphorylation in Bcr-Abl oncogenic eects. Our results indicate that Jak2 became tyrosine-phosphorylated in a number of cell lines expressing Bcr ± Abl, when maintained in medium lacking IL-3, whereas Bcr ± Abl negative cells lacked Jak2 tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 26 publications
9
161
0
Order By: Relevance
“…Previous findings by two groups have shown that Stat5 activation is directed by Bcr-Abl oncoprotein (Ilaria and Van Etten, 1996;Klejman et al, 2002). Our previous studies indicate that Stat5 activation is independent of Jak2 activation in BCR-ABL þ 32D cells (Xie et al, 2001), which is in agreement with the earlier findings of Ilaria and Van Etten (1996).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous findings by two groups have shown that Stat5 activation is directed by Bcr-Abl oncoprotein (Ilaria and Van Etten, 1996;Klejman et al, 2002). Our previous studies indicate that Stat5 activation is independent of Jak2 activation in BCR-ABL þ 32D cells (Xie et al, 2001), which is in agreement with the earlier findings of Ilaria and Van Etten (1996).…”
Section: Discussionsupporting
confidence: 93%
“…Since the expression of the IL-3 receptor chains was critical for the oncogenic transformation of NIH 3T3 cells by BCR-ABL, we asked whether Jak2 is involved in the oncogenic behavior of these cells. We have previously shown that mouse and human BCR-ABL þ hematopoietic cells require Jak2 for the expression of the oncogenic phenotype (Xie et al, 2001(Xie et al, , 2002Samanta et al, 2006). Importantly, Jak2 plays a critical role in activating the PI-3 kinase, Akt, and NF-kB and inactivating GSK3-b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This BCR-ABLdependent phosphatidylinositol 3-kinase activation is in part mediated by GAB2 and/or c-CBL (Sattler et al, 1996;Chu et al, 2007). Furthermore, STAT5, which regulates CYCLIN D1 and BCL-xL, is activated by BCR-ABL independent of Jak family proteins (Xie et al, 2001). STAT5a/b-deficient fetal liver hematopoietic progenitors fail to generate leukemia in recipient mice after retroviral transduction with BCR-ABL (Hoelbl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%